Joan Rockwell: Evald Tang Kristensen. A lifelong adventure in folklore. (Aalborg Studies in Folk Culture, No. 5. Aalborg University Press /Danish Folklore Society, 1982). XXXVII + 415 s. - Chr. Manniche, Jens (Historie/Jyske Samlinger, 1985)
-